PERBEDAAN HASIL BELAJAR KIMIA MELALUI PEMBELAJARAN KOOPERATIF TIPE BUZZ GROUP DENGAN TIPE STAD DALAM POKOK BAHASAN IKATAN KIMIA PADA SISWA KELAS X SMAN 4 PASANGKAYU - Etty Etty; Suherman Suherman; Supriadi Supriadi (Jurnal Akademika Kimia, 2013)
This research aimed to determine the differences in student outcomes that given cooperative model of Buzz group type with STAD type in students ofclass X SMA Negeri 4 Pasangkayu. Sample used consists of two classes, namely class XB as Buzz class group and class XA as STAD classes were determined by purposive sampling. Data collection was conducted using a test instrument, be in the form of student achievement test chemistry in the form (multiple choice) as many as 30 items. Testing research data using statistical analysis t test (right side) with the prerequisite test, test for normality, and homogeneity. In this research obtained the median of student learning outcomes using learning Buzz groupmodel was 19.56 while median of student learning outcomes with STAD cooperative model is 16.46. Based on statistical hypothesis testing with t test statistic (right) obtained values of thitung > ttabel was 1.771 > 1.67 with the degree of freedom = 0.05 and df = 59. The results showed that there was a difference in student learning outcomes using cooperative learning group Buzz type with student learning outcomes using STAD type cooperative.